Designing with the mind in mind : sample guide to understanding user interface design guidelines - Johnson, Jeff (Cambridge : Morgan Kaufman, 2021)
User interface (UI) design rules and guidelines, developed by early HCI gurus and recognized throughout the field, were based on cognitive psychology (study of mental processes such as problem solving, memory, and language), and early practitioners were well informed of its tenets. But today practitioners with backgrounds in cognitive psychology are a minority, as user interface designers and developers enter the field from a wide array of disciplines. HCI practitioners today have enough experience in UI design that they have been exposed to UI design rules, but it is essential that they understand the psychological basis behind the rules in order to effectively apply them.
Chapter 1. Our perception is Biased -- Chapter 2. Our Vision is Optimized to see structure -- Chapter 3. We seek and use visual structure -- Chapter 4. Our color vision is limited -- Chapter 5. Our peripheral vision is limited -- Chapter 6. Reading is unnatural -- Chapter 7. Our attention is Limited; Our Memory is imperfect -- Chapter 8. Limits on attention shape our thought and action -- Chapter 9. Recognition is easy; Recall is Hard -- Chapter 10. Learning from experience and performing learned actions are easy -- Chapter 11. Many factors affect learning -- Chapter 12. Human Decision-Making is rarely rational -- Chapter 13. Our hand-eye coordination follows laws -- Chapter 14. We have time requirements -- Chapter 15. We make errors.
Includes bibliographical references and index.
Keywords: GRAPHICAL USER INTERFACES (COMPUTER SYSTEMS)